Engineering of monodisperse core–shell up-conversion dendritic mesoporous silica nanocomposites with a tunable pore size. Issue 8 (18th February 2020) - Dai, Yu; Yang, Dongpeng; Yu, Danping; Xie, Songhai; Wang, Biwei; Bu, Juan; Shen, Bin; Feng, Wei; Li, Fuyou
Abstract : We developed a general method to obtain upconversion nanoparticle-based nanocomposites by coating a mesoporous silica layer as the loading matrix. Abstract : Fabricating lanthanide doped up-conversion luminescence based nanocomposites has drawn increasing attention in nanoscience and nanotechnology. Although challenging in precise synthesis, structure manipulation and interfacial engineering, fabricating dendritic mesoporous silica coated up-conversion nanoparticles (UCNP@dMSNs) with a tunable pore size is of great importance for the functionalization and application of UCNPs. Herein, we report a strategy to prepare uniform monodisperse UCNP@dMSNs with a core–shell structure. The silica shell has tunable center-radial and dendritic mesoporous channels. The synthesis was carried out in the heterogeneous oil–water microemulsion phase of the Winsor III system reaction system, which allows silica to be deposited directly on hydrophobic UCNPs through the self-anchoring of micelle complexes on the oleic acid ligand. The average pore size of UCNP@dMSNs could be tailored from ∼10 to ∼35 nm according to the varied amounts of co-solvent in the mixture. The microemulsion approach could also be used to prepare hierarchical UCNP@dMSNs with a multi-generational mesostructure. The resultant UCNP@dMSNs exhibit the unique advantage of loading "guest" nanoparticles in a self-absorption manner. We proved that Cu1.8 S NPs (∼10 nm), Au NPs (∼10 nm) and Fe3 O4 NPs (∼25 nm) could be incorporated in UCNP@dMSNs, which in turn validates the high adsorption capacity of UCNP@dMSNs.